Three series π-extended fluorescent compounds based on dehydroabietic acid triarylamine moiety: Syhthesis, photophysical properties and hole transporting properties. (October 2020) - Tan, Guanni; Song, Jie; Zhang, Xinwen; Gao, Yanan; Shang, Shibin; Song, Zhanqian; Gao, Hong
Abstract: Fluorescent compounds based on a dehydroabietic acid skeleton with favorable photophysical properties show promise for use as the hole-transporting layer in organic light-emitting diodes (OLEDs). In this work, we report the synthesis of three series of compounds (15 in total), series 1 (1a –1e ), series 2 (2a –2e ), and series 3 (3a –3e ), by linking polycyclic aromatic hydrocarbons (PAHs) to dehydroabietic acid-based triaryamine moiety through C-C coupling reactions. The three series of compounds exhibited ultraviolet absorption, fluorescence emission, electrochemical, and thermal properties, as well as highest occupied molecular orbital levels and energy gaps that made them suitable for use as hole-transporting materials. OLEDs with 1a, 2a, or 3d as a hole-transporting layer showed better performance in terms of maximum brightness, turn-on voltage, maximum of external quantum efficiency, maximum luminous efficiency and power efficiency than that of a comparable device based on a conventional hole-transporting material. In particular, the device with 1a exhibited the most promising performance, with a high maximum brightness of 21445 cd/m 2, low turn-on voltage of 2.8 V, maximum of external quantum efficiency of 1.62%, maximum luminance efficiency of 4.9 cd/A, and maximum power efficiency 3.7lm/W. The present work highlights the potential of π-extended compounds based on dehydroabietic acid for use in luminescent material applications. Graphical abstract: Image 1 Highlights: Three series π-extended fluorescent compounds based on dehydroabietic acid triarylamine moiety were synthesized. The compounds exhibited good photophysical properties, electrochemical properties, and thermal properties. HOMO levels and energy gaps determined experimentally and theoretically were in good agreement. Some compounds as a hole-transporting layer in OLEDs showed excellent performance.